Rap: o duelo de rimas no cotidiano do jovem - Tejera, Daniel Bidia Olmedo [UNESP] (2013)
This research will focus on the “Batalha Central”, an event that happens every month at downtown of Piracicaba / SP in which admirers of Hip-hop culture and Rap music come together to fight duels rhymes in a playful way. The objective of this study is to identify if the Hip-hop – specifically Rap battles in the context of improvisation – may or may not can contribute to development of the participant, especially critical and creative and to check the influence cultural precepts of the Hip-hop can have on participants. The Hip-hop emerges from an urban context, created by young blacks and caribbean immigrants as a form of cultural expression, in the district of the Bronx, New York, United States in the 60s. In order to transform the gang violence in disputes healthy, Afrika Bambaataa – one of the main organizers of block parties – began to organize such parties aiming to convert the strife in duels involving artistic expressions divided into four elements: Mc, Dj, Break and Graphite. The merger between the Mc and Dj Rap originated. The type of Rap that we discuss in this study is the impromptu Rap, sort of challenge based on oral poetry and improvisation, a mechanism similar to that found in brazilian “Repente”. This is a qualitative research is characterized by a case study and exploration. To obtain data, were used for semistructured interviews, document analysis and participant observation, in addition to a previous literature. Through this study it was possible to understand the influence exerted by the precepts of Hip-hop in the lives of young people participating in this leisure practice, which will probably end up supplying some needs unmet at school, or other follow-up of society, in addition to understanding a little about how specifically the battles of Mc `s interferes with the development of creativity and criticality of the practitioner